Driving Factors Influencing International Affluent Tourists' Decision in Wellness Tourism in the Eastern Economic Corridor: A Case Study of Chonburi Province - Pinthong, Chitlada; Rodhring, Kamolwan (Journal of Applied Economics and Management Strategy, 2025)
Wellness tourism is one of the fastest-growing trends in the tourism industry, as people increasingly prioritize health and quality of life. Thailand is a prominent country in wellness tourism, particularly in Southeast Asia, due to its rich natural resources, unique cultural heritage, and high-quality medical services at competitive prices. Chonburi Province, renowned for its tourist attractions, not only boasts stunning beaches and diverse travel destinations but also provides comprehensive health services. This research aims to examine the push and pull motivations of high-income tourists influencing their decision to engage in health tourism in Chonburi. The findings will serve as a guideline for effectively planning the development of health tourism to better meet the needs of international high-income tourists. Push motivation refers to intrinsic factors that stimulate individuals to undertake travel, whereas pull motivation pertains to external attributes of a destination that attract travelers in response to their internal drives. This study employed a quantitative research approach, utilizing a survey questionnaire to collect data from 356 high-income international tourists visiting Chonburi for health tourism with sampling method applied as Quota Sampling. The data were analyzed using descriptive statistics, One-Way ANOVA to examine mean differences, paired comparisons with LSD, and multiple linear regression analysis. The results revealed that age, education, occupation, income, and nationality significantly influenced the motivations of affluent tourists participating in wellness tourism. Furthermore, both push and pull factors positively impacted the decision-making process of affluent international tourists in choosing Chonburi as a wellness tourism destination.